2019
DOI: 10.1155/2019/1578502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serum Glucose on the Predictive Value of Serum Lactate for Hospital Mortality in Critically Ill Surgical Patients

Abstract: Background Lactate has been widely used as a risk indicator of outcomes in critically ill patients due to its ready measurement and good predictive ability. However, the interconnections between lactate metabolism and glucose metabolism have not been sufficiently explored, yet. In this study, we aimed to investigate whether glucose levels could influence the predictive ability of lactate and design a more comprehensive strategy to assess the in-hospital mortality of critically ill patients. Methods We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 9 An elevated lactate level is a poor indicator of survival in critically ill patients. 10 , 11 However, whether it is an independent risk factor for mortality in surgical ICU remains unknown. Thus, there is an urgent need for evaluations of risk factors associated with mortality in surgical ICU.…”
Section: Introductionmentioning
confidence: 99%
“… 9 An elevated lactate level is a poor indicator of survival in critically ill patients. 10 , 11 However, whether it is an independent risk factor for mortality in surgical ICU remains unknown. Thus, there is an urgent need for evaluations of risk factors associated with mortality in surgical ICU.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality is strongly correlated with blood glucose and serum lactate levels. A study of critically ill patients (Chen et al 2019) found that the mortality rate was approximately 23% when serum lactate was higher than 2.3mmol/l and approximately 10% when blood glucose was lower than 70mg/dL (Freire Jorge et al 2017). During the first 24h after admission, the coincidence of low glucose and high serum lactate was associated with a high risk of acute kidney injury, liver dysfunction, and hospital mortality (Freire Jorge et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Interestingly, Chen et al reveal an extended impact of the blood glucose levels on the inhospital mortality predictive value of serum lactate in critically ill surgical subset. 7 Chen et al describe that the serum lactate levels predicts mortality in the hypoglycemic (<7 mmol/L) and the hyperglycemic groups (>9 mmol/L) but not in the normoglycemic (7-9 mmol/L) study group. 5,7 The concerns about neonatal organ immaturity concomitant with low-flow states also complicate the authors' analysis.…”
Section: To the Editormentioning
confidence: 99%
“…7 Chen et al describe that the serum lactate levels predicts mortality in the hypoglycemic (<7 mmol/L) and the hyperglycemic groups (>9 mmol/L) but not in the normoglycemic (7-9 mmol/L) study group. 5,7 The concerns about neonatal organ immaturity concomitant with low-flow states also complicate the authors' analysis.…”
Section: To the Editormentioning
confidence: 99%